Logistic ways of handling domestic medicines of derivatives etilmetilgidroksipiridina succinate at the regional pharmaceutical market - I. I. Pavlyuchenko; N. M. Bat (Кубанский научный медицинский вестник, 2015)
Disorders of hypoxic and free radical origin as they rise can lead to the destruction of cells and, consequently, often determine the fate of the organ, tissue and ultimately the whole organism. Hence, the relevance of using high-performance antihypoxants and antioxidants in individual and complex schemas, standards of disease treatment. The aim of the study was to determine the logistics of the ways of treatment and the intensity of use of drugs of etilmetilgidroksipiridina succinate for antioxidant therapy in a particular region to represent the common aspects of their application.